Cover Feature: Switching of Monomer Fluorescence, Charge‐Transfer Fluorescence, and Room‐Temperature Phosphorescence Induced by Aromatic Guest Inclusion in a Supramolecular Host (Chem. Eur. J. 66/2018). Issue 66 (21st November 2018) - Ono, Toshikazu; Taema, Ai; Goto, Aiko; Hisaeda, Yoshio
Abstract : Ternary‐component crystals with guest‐dependent photofunctions, such as crystallization‐induced enhanced emission, intermolecular charge‐transfer emission, and room‐temperature phosphorescence emission under UV‐light irradiation, have been designed. The single‐crystal X‐ray structure determination of eight different guest crystals was performed, and the structure–property relationships at a molecular level were studied. The findings provide important guidelines for the future design of novel optoelectronic organic materials. More information can be found in the Full Paper by T. Ono, Y. Hisaeda et al. onpage 17487 .